URGENSI IJTIHAD AKADEMIK DALAM MENJAWAB PROBLEMATIKA MUAMALAH KONTEMPORER - Kholis, Nur (Islamic University of Indonesia, 2005)
The article below traces to find the urgency of academic ijtihad to solve contemporary problems in muamalah (transaction). The age of globalization supported by information technologies revolusion makes all aspects of human life changes rapidly especially in economic activities. Many kinds and aspects of transaction that human did not think many years ago, occur in this era, for instance insurance, electronic banking, e-commerce, capital market, unit trust, etc. All forms of transaction in this era need to be solved and justified by Islamic law in order to all muslims in the world can participate in economic activities among other people at global era. Islam as the last religion revealed by Allah SWT has many tools to anticipate and solve contemporary problems occurring in the global era. Al-Quran and alSunnah as the main sources of Islamic law provide tools to make Islamic teachings always suitable for all time, namely by academic ijtihad. By doing academic ijtihad to solve contemporary muamalah problems in this global era will make Islamic law always appropriate whenever and wherever. Kata Kunci: Ijtihad akademik, problematika, fiqh muamalah kontemporer